Genital morphology associated with mating strategy in the polymorphic lizard, Uta stansburiana. (28th December 2018) - Gilman, Casey A.; Corl, Ammon; Sinervo, Barry; Irschick, Duncan J.
Abstract: Sexual selection can lead to rapid evolution of sexual traits and striking morphological diversity across taxa. In populations where competition for mates is intense, males sometimes evolve distinct behavioral strategies along with morphological differences that help them secure mating opportunities. Strong postcopulatory selection and differential resource allocation across male strategy type can result in strategy‐specific differences in sexual traits, such as sperm morphology, ejaculate components, and testis size. Some polymorphic species also have strategy‐specific genital morphology. Thus far, among vertebrates, this has only been observed in fish. Here, we present the first morphological description of the intromittant copulatory organ, the hemipenis, of the three mating types of the side‐blotched lizard, Uta stansburiana, from a population that exhibits alternative mating strategies. We found that the isometrically scaling hemipenis was shortest in the nonterritorial (yellow) morph that sneaks copulations with other males' mates. Although the hemipenes were generally the same shape across morphs, the usurping territorial (orange) morph had a significantly wider apical horn than the nonterritorial sneaker morph. Sneaker males also had smaller relative body masses than both the mate‐guarding (blue) morph and the usurper morph, and shorter tibia than the usurper morph. This study using a small sample of males suggests that strong sexual selection may drive genital trait differentiation across morphs within populations of terrestrial vertebrates. Abstract : We found differences in genital length and ornamentation across morphs within a population of lizards exhibiting alternative mating strategies. This lizard has previously shown to have morph‐specific morphology, physiology, and behavior.